Self-formation of dual glassy-crystalline structure in magnetron sputtered W–Zr films. (May 2021) - Zeman, P.; Haviar, S.; Červená, M.
Abstract: Self-formation of a unique dual glassy-crystalline structure in binary W–Zr system was observed for a film with 28 at.% Zr prepared by magnetron co-sputtering. The film is composed of conical columnar domains of α-W(Zr) solid solution structure surrounded by featureless areas corresponding to a W–Zr metallic glass. The conical domains have their axes perpendicular to the film surface. Most of the domains have the apex at or close to the substrate surface, which corresponds to the point of primary nucleation. The surface ratio of glassy and crystalline phase (bases of the cones) is dependent on the film thickness. The dual structure is prepared in a very narrow window of the elemental composition. We suppose that the specific elemental composition and the diffusivity or mobility of sputtered adatoms are crucial for the self-formation of the dual structure. Highlights: Self-formation of a dual glassy-crystalline structure in binary W–Zr system was observed. The unique dual structure is prepared by magnetron sputtering at around 28 at.% Zr. The structure is composed of columnar domains surrounded by a W–Zr metallic glass. The domains are crystalline with an α-W(Zr) solid solution structure. The domains grow in cones with the axes perpendicular to the film surface.